CityLayers: A GIS Integrated Framework towards the Sustainable Smart Cities Approach - Bhagat, Maulik; Gaikwad, Santosh; Kanani, Rahul; Odedra, Arjan; Sodhi, Aashima (International Journal of Computer Sciences and Engineering, 2022)
The advent of smart cities aims to alleviate the challenges concerned with the ongoing urbanization and rising population density. To achieve the necessary degree of sustainability, government is looking for smart and efficient solutions for effective smart city data management. Such smart city decisions are based upon near real-time handling of a city’s needs, proper planning and better finance in various municipal sectors. This requires a need for a new generation GIS enabled Decision Support System (DSS) for more efficient Municipal e-Governance. In order to enable holistic planning and functionality of a city with high visual impact, municipalities, especially in developing countries, often lack proper integrated tools to analyse their broad spectrum of information. To address these issues, the present study strives to provide holistic solutions to the e-governances, by the virtue of Information Computing Technology (ICT), on the basis of a developed product called CityLayers, which is fully integrated with e-Governance applications. The product has been established using open source technologies and has been customized to handle vast Municipal datasets with effective geo- data visualization. The product is compliant to Open Geospatial Consortium, and is a cross- platform, cross-device in nature providing quick access to spatial data, visualization and analytical capabilities over a web browser.